ETHNO-STEM BERBASIS PENGETAHUAN LOKAL DALAM MENINGKATKAN LITERASI EKOLOGIS SISWA MADRASAH IBTIDAIYAH - Andrian Gandi Wijanarko; Yoga Dwi Prada; Tyas Maharani (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
The low level of ecological understanding among elementary school students is one of the obstacles to implementing education that supports environmental sustainability. On the other hand, the diverse traditional knowledge that thrives in the Temanggung community is actually very useful as teaching materials tailored to local conditions, but has not been optimally utilized in school teaching and learning activities. This study aims to describe how to implement Ethno-STEM learning that relies on local wisdom and examine its impact on improving students' environmental literacy at MI Al Ikhlas Parakan. This research used qualitative methods with a case study design. Data collection was conducted through direct observation, in-depth interviews with teachers, students, and community leaders, and a review of teaching materials. The data obtained were then processed through stages of simplification, systematic presentation, and drawing conclusions, cross-checking with various sources and methods to ensure the accuracy of the information. The results revealed that incorporating Temanggung community wisdom, such as traditional farming methods, natural resource management, and habits of maintaining environmental balance, helped students understand environmental concepts in a concrete and meaningful way. The Ethno-STEM approach enables students to connect science, technology, engineering, and mathematics lessons with the environmental conditions around them. This ultimately fosters students' awareness, concern, and sense of responsibility for preserving nature. Students' active participation in the learning process also appears to improve their environmentally friendly knowledge, attitudes, and actions. Therefore, Ethno-STEM learning based on local wisdom can be an effective strategy for improving students' environmental literacy at MI Al Ikhlas Parakan, while simultaneously preserving the cultural heritage values ​​of the Temanggung culture.